Report on Study of Viability of Priliminary Agricultural Credit Societies A Bench Mark Survey (1968-69) - Planning Commission (Planning Commission, 1973)
This summary synthesizes the findings of the 1973 Apte Report on the viability of Primary Agricultural Credit Societies (PACS) and related state-wise agricultural finance data in India. It examines the structural framework, financial performance, loan distribution patterns, and regional disparities within the cooperative credit system. The analysis highlights issues of low capital base, high overdue loans, limited distribution of agricultural inputs, and uneven financial support across states, while underscoring the need for improved data systems and targeted policy interventions to strengthen agricultural credit delivery.
Government of India Planning Commission New Delhi 1973
Government of India Planning Commission New Delhi 1973
Keywords: Primary Agricultural Credit Societies; Cooperative Credit System; Agricultural Finance; Loan Distribution; Financial Viability; Overdue Loans; Share Capital; Agricultural Requisites; Regional Disparities; Policy Planning